Enhanced visible-light photocatalytic activity of g-C3N4/TiO2films - Natkritta Boonprakob (2018)
Enhanced photocatalytic degradation of methylene blue (MB) using graphitic carbon nitride/titanium dioxide (g-C 3 N 4 /TiO 2 ) catalyst films has been demonstrated in this present work. The g-C 3 N 4 /TiO 2 composites were prepared by directly heating the mixture of melamine and pre-synthesized TiO 2 nanoparticles in Ar gas flow. The g-C 3 N 4 contents in the g-C 3 N 4 /TiO 2 composites were varied as 0, 20, 50 and 70wt%. It was found that the visible-light-induced photocatalytic degradation of MB was remarkably increased upon coupling TiO 2 with g-C 3 N 4 and the best degradation performance of ~70% was obtained from 50wt%g-C 3 N 4 loading content. Results from UV-vis absorption study, Electron microscopy, Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy suggest that the improved photoactivity is due to a decrease in band gap energy, an increased light absorption in visible light region and possibly an enhanced electron-hole separation efficiency as a result of effective interfacial electron transfer between TiO 2 and g-C 3 N 4 of the g-C 3 N 4 /TiO 2 composite film. Based on the obtained results, the possible MB degradation mechanism is ascribed mainly to the generation of active species induced by the photogenerated electrons. © 2013 Elsevier Inc.